Antibacterial Test of Teki Grass Extract (Cyperus Rotundus) in Inhibiting Escherichia Coli and Salmonella Typhi - Sartini Sartini; Rahmiati Rahmiati; Selvi Herliyani; Riyanto Riyanto; Ellen L. Panggabean; Saipul Sihotang (Postgraduate, University of Mataram, 2023)
This study aims to determine the antibacterial ability of Cyperus rotundus extract in inhibiting the growth of Escherichia coli and Salmonella typhi by measuring the diameter of the inhibition zone. This research method used a completely randomized design (CRD) and LSD test as a follow-up test with one factor, namely variations in the concentration of C. rotundus extract 20%, 40%, 60%, 80% and 100%, distilled water as a negative control and the antibiotic chloramphenicol as a positive control. The results showed that the extract of C. rotundus could inhibit the growth of Escherichia coli with the largest inhibition zone diameter indicated by a concentration of 100% which was 2.33mm and the smallest inhibition zone diameter was found at a concentration of 20%, namely 1.00 mm. While in Salmonella typhi the largest inhibition zone was shown at a concentration of 100%, namely 3, 03mm and the smallest inhibition zone was indicated by a concentration of 20%, namely 1.07 mm. The results of the ANOVA and LSD tests with 95% confidence test showed that there was a difference in the average diameter of the inhibition zone in each treatment with variations in the concentration of C. rotundus extract with a concentration of 80% as the most effective.